2017
DOI: 10.1177/1010428317705506
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA MSTO2P promotes the proliferation and colony formation in gastric cancer by indirectly regulating miR-335 expression

Abstract: Long non-coding RNAs are emerging as new players in gene regulation, but whether long non-coding RNAs influence the expression of microRNA is unclear. The expression levels of misato family member 2, pseudogene were significantly associated with lymphatic metastasis and distal metastasis in 80 paired gastric cancer tissues using real-time quantitative reverse transcription polymerase chain reaction experiments. The effects of long non-coding RNA misato family member 2, pseudogene were assessed by overexpressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Despite the identification of a number of miRNA targets involved in human tumors, in the majority of cases their mechanisms of effect remain unclear. The expression of miR‐335 has been shown to be aberrant in tumor tissue from several types of cancer, and is associated with cell proliferation and inflammation . The present study found that miR‐335 was downregulated in NSCLC tumor tissues compared with adjacent non‐tumor tissues.…”
Section: Discussionsupporting
confidence: 52%
“…Despite the identification of a number of miRNA targets involved in human tumors, in the majority of cases their mechanisms of effect remain unclear. The expression of miR‐335 has been shown to be aberrant in tumor tissue from several types of cancer, and is associated with cell proliferation and inflammation . The present study found that miR‐335 was downregulated in NSCLC tumor tissues compared with adjacent non‐tumor tissues.…”
Section: Discussionsupporting
confidence: 52%
“…Until now, numerous studies have proved that lncRNAs were highly active in plenty of pathological processes of GC, such as proliferation and metastasis. Among them, some lncRNAs were de ned as protective factors while others were risk factors [25,[41][42][43][44]. Furthermore, several studies have proved that lncRNAs participated in the progression, especially malignant progression of GC through regulating autophagy-related mRNAs [24][25][26][27][28][29]45].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Xu et al, (2012) found down regulation of miR-335 in gastric cancer, they reported that lymph node metastasis, poor pT stage, poor pN stage, and invasion of lymphatic vessels, was significantly associated with low expression of miR-335, suggesting a metastasis suppressor function of miR-335 in this disease. miR-335 has been demonstrated to play important roles gastrointestinal tract cancer including GBC (Li et al, 2017;Zhang et al, 2018;Feng et al, 2018;Lu et al, 2016;Zhang et al, 2014). However there has been scarcity of studies on GBC showing the prognostic and therapeutic importance of miR-335.…”
Section: Discussionmentioning
confidence: 99%